1995
DOI: 10.1523/jneurosci.15-09-05976.1995
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural immunolabeling shows prominent presynaptic vesicular localization of delta-opioid receptor within both enkephalin- and nonenkephalin-containing axon terminals in the superficial layers of the rat cervical spinal cord

Abstract: Opioid peptides, Met5- and Leu5-enkephalin, are known endogenous ligands for the delta-opioid receptor (DOR) associated with opioid analgesia at the spinal level. To determine the cellular sites for DOR-mediated actions, we examined the ultrastructural localization of DOR and Met5-enkephalin (ME) in the spinal cord by combining immunoperoxidase and immunogold-silver labeling for antibodies against DOR and ME, respectively. Antibodies for DOR localization were raised in guinea pig against peptide 34-47 (p34), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
115
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 55 publications
15
115
4
Order By: Relevance
“…Some of these changes affect the expression and subcellular distribution of dOR in neurons of the dorsal horn of the spinal cord and dorsal root ganglia (Besse et al, 1992;Cahill et al, 2003;Ji et al, 1995). Under basal conditions, dOR are almost exclusively localized to intracellular compartments in neurons throughout the CNS, including the spinal cord (Arvidsson et al, 1995;Cahill et al, 2001a,b;Cheng et al, 1995;Morinville et al, 2003;Svingos et al, 1995;Wang and Pickel, 2001;Zhang et al, 1998). Hence, ultra-structural analysis revealed that in the rat spinal cord, plasma membrane-associated dOR accounted for less than 10% of the total amount of immunoreactive dOR detected within dendrites of dorsal horn neurons (Cahill et al, 2001a,b;Morinville et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these changes affect the expression and subcellular distribution of dOR in neurons of the dorsal horn of the spinal cord and dorsal root ganglia (Besse et al, 1992;Cahill et al, 2003;Ji et al, 1995). Under basal conditions, dOR are almost exclusively localized to intracellular compartments in neurons throughout the CNS, including the spinal cord (Arvidsson et al, 1995;Cahill et al, 2001a,b;Cheng et al, 1995;Morinville et al, 2003;Svingos et al, 1995;Wang and Pickel, 2001;Zhang et al, 1998). Hence, ultra-structural analysis revealed that in the rat spinal cord, plasma membrane-associated dOR accounted for less than 10% of the total amount of immunoreactive dOR detected within dendrites of dorsal horn neurons (Cahill et al, 2001a,b;Morinville et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these genes is expressed in neurons in several neuronal circuits implicated in nociception (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which each of the three opiate receptor subtype gene products might participate in different features of opiate-or morphineinduced analgesia thus has remained unclear. Elucidation of the selective analgesic contributions of each opiate receptor subtype is of substantial potential importance for developing improved analgesic medications with minimal undesirable effects.Expression of endogenous opioid-peptide agonists, especially those derived from the preproenkephalin and preprodynorphin genes, in circuits associated with pain perception suggests that opioid-peptide interactions with opiate receptors could be well positioned to modulate nociceptive responses in the absence of exogenously administered opiate drugs (10,12,14,(27)(28)(29)(30)(31)(32). Studies of pain responses in animals and humans treated with opiate antagonists, however, have documented modifications in nociception in some but not all studies (33,34).…”
mentioning
confidence: 99%
“…By contrast, drugs acting on ␦OR produce more limited analgesia, but also give rise to considerably less undesirable side-effects and induce virtually no tolerance (Porreca et al, 1984;May et al, 1989; Sheldon et al, 1990;Szeto et al, 1999;Gallantine and Meert, 2005). For these reasons, ␦OR agonists have been proposed as possible alternatives to OR agonists for the treatment of chronic pain, including neuropathic (Mika et al, 2001;Petrillo et al, 2003;Morinville et al, 2004a) and chronic inflammatory pain (Desmeules et al, 1993;Stewart and Hammond, 1994;Fraser et al, 2000;Hurley and Hammond, 2000;Qiu et al, 2000;Cahill et al, 2003;Petrillo et al, 2003).One of the reasons for the relatively poor analgesic efficiency of ␦OR agonists may be that only a small proportion of ␦OR is actually present on neuronal plasma membranes under baseline conditions (Cheng et al, 1995(Cheng et al, , 1997Elde et al, 1995;Zhang et al, 1998;Cahill et al, 2001a). However, under conditions of chronic inflammation, such as produced in rodents by injection of complete Freund's adjuvant (CFA) in the hind paw, we observed a massive recruitment of ␦OR from intracellular stores to the plasma membrane in neurons of the dorsal horn of the spinal cord Morinville et al, 2004b).…”
mentioning
confidence: 99%
“…One of the reasons for the relatively poor analgesic efficiency of ␦OR agonists may be that only a small proportion of ␦OR is actually present on neuronal plasma membranes under baseline conditions (Cheng et al, 1995(Cheng et al, , 1997Elde et al, 1995;Zhang et al, 1998;Cahill et al, 2001a). However, under conditions of chronic inflammation, such as produced in rodents by injection of complete Freund's adjuvant (CFA) in the hind paw, we observed a massive recruitment of ␦OR from intracellular stores to the plasma membrane in neurons of the dorsal horn of the spinal cord Morinville et al, 2004b).…”
mentioning
confidence: 99%